EXPLORACION BIOLOGICA POR LA CUENCA DEL RIO TAMAZULA - GONZALES ORTEGA, J (My University, 1927)
EXPLORACION BIOLOGICA POR LA CUENCA DEL RIO TAMAZULA
MEM SOC CIE ANTONIO ALZATE
Keywords: EXPLORACION, BIOLOGICA, CUENCA, RIO, TAMAZULA; MULTIDISCIPLINARIA